Stimulasi Verbal Orang Tua sebagai Faktor Kunci yang Mempengaruhi Perkembangan Bahasa Awal pada Bayi - Mariana Putri Sholihah; Koekoeh Hardjito; Finta Isti Kundarti; Ririn Indriani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Language ability is a crucial aspect of child development, yet language delay remains a common issue both globally and nationally, including in the Tanon Primary Health Center area. This study aimed to analyze the relationship between parental verbal stimulation and language development in infants aged 6–12 months. An analytic observational study with a cross-sectional design was conducted in May–June 2025, involving 41 parents and their infants selected through proportionate stratified random sampling. Data were collected using a validated verbal stimulation questionnaire (α = 0.767) and expert-validated language development observation sheets (validity score = 0.8295). Results showed that parental verbal stimulation was categorized as good (48.78%), fair (43.9%), and poor (7.32%). Infant language development outcomes were very well developed (36.59%), as expected (26.83%), emerging (21.95%), and not yet developed (14.63%). Spearman Rank correlation indicated a significant association between parental verbal stimulation and infant language development (p = 0.02). The findings highlight the importance of consistent early verbal stimulation supported by healthcare workers through education and counseling at community health posts (Posyandu) to prevent language delay.